2021
DOI: 10.1080/26895293.2021.1911862
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and screening of microalgal species, native to Zimbabwe, with potential use in biodiesel production

Abstract: Microalgae are increasingly being preferred as sustainable biomass feedstock for biofuels production due to their high growth rate and lipid yield. However, optimal production requires the use of economical native microalgal species which are well adapted to local climatic and ecological conditions. Therefore, this study's main objective was to isolate and select local microalgal species for prospective biofuels production. Serial dilution and streak plate techniques were used to isolate four species: Chlorell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…In a study carried out by Taziki et al (2015), it was revealed that the microalgae were able to remove nitrates and nitrites from wastewater by assimilation. In Zimbabwe, Sero et al (2021) isolated and selected four microalgae native to Zimbabwe with potential use in biodiesel production. These were Chlorella spp, Oscillatoria spp.…”
Section: Advantages Of Bioremediation Have Been Explicitly Explained Bymentioning
confidence: 99%
“…In a study carried out by Taziki et al (2015), it was revealed that the microalgae were able to remove nitrates and nitrites from wastewater by assimilation. In Zimbabwe, Sero et al (2021) isolated and selected four microalgae native to Zimbabwe with potential use in biodiesel production. These were Chlorella spp, Oscillatoria spp.…”
Section: Advantages Of Bioremediation Have Been Explicitly Explained Bymentioning
confidence: 99%
“…showed good adaptability to new environment, highest growth rate, and high lipid productivities which are important selection criteria in biorefinery applications. [ 25 ]…”
Section: Screening Of Microalgal Strains For Integrated Biorefinery A...mentioning
confidence: 99%
“…showed good adaptability to new environment, highest growth rate, and high lipid productivities which are important selection criteria in biorefinery applications. [25] www.clean-journal.com Chlorella vulgaris and Dictyosphaerium sp. were screened on process water from pulp and paper mill as microalgal cultivation medium for biorefinery applications and biomass/lipid production.…”
Section: Culture-based Techniquesmentioning
confidence: 99%
“…It is often argued that indigenous strains have better fitness to grow in that local environment (Winckelmann et al, 2015;Mutanda et al, 2020). Sero and colleagues reported that the microalgal strains isolated from extreme urban wastewater environments have inherent biological traits to proliferate in stress and capable of producing high biomass yield using wastewater (Sero et al, 2021). Adaptive evolution, mutagenesis, genetic engineering, and systems biology approaches have been used now for microalgal strain improvement with desired traits (Arora and Philippidis, 2021;Kumar Singh et al, 2021;LaPanse et al, 2021).…”
Section: Sustainable Cultivation Practicesmentioning
confidence: 99%